The fundamentals of marketing - Russel, Edward (Ava Academia, 2010)
Introduces the fundamentals of marketing communications to non-business students. This book teaches students how marketing organisations successfully move from product concept through to successful brand and the tools used to make brands as strong as they can be. It shows how these tools are used to develop successful marketing communications